Efectos del ejercicio físico en la autoestima de cinco jóvenes entre 18 Y 30 años que asisten a gimnasios del municipio de Zarzal, Valle del Cauca - Jalil Peréz, Cristian (Universidad Antonio Nariño, 2022)
The present research is characterized by being descriptive, that is to describe the phenomena or situations of a study, in this case to describe the effects or influence that the Fitness activity can have on the self-concept and self-image of the 5 participants. Likewise, within the present investigation for the collection of the information it is not going to manipulate variables, which is another of the characteristics of a descriptive investigation, since these variables are already defined in this case physical activity and self-esteem, and on which the study is going to be carried out, since they were applied to instruments such as the interview and the rosemberg scale it can be said then that it is a mixed investigation, In general, In general, the results are expected to be positive because the tools applied from participant 1 to participant 5 can be highlighted according to the Rosemberg scale and the interview that in the pre-application there were low scores and negative verbalizations which indicated at first low self-esteem, the second point of application that was carried out 4 months later, the results are elevated in contrast to the first and changes the negative verbalizations leaving to see favorable changes.